2019
DOI: 10.3892/ol.2019.10077
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of cell division cycle‑associated protein 4 expression inhibits proliferation of triple negative breast cancer MDA‑MB‑231 cells in�vitro and in�vivo

Abstract: Cell division cycle-associated protein 4 (CDCA4), also known as SEI-3/hematopoietic progenitor protein, is a target gene of transcription factor E2F and represses E2F-dependent transcriptional activation and cell proliferation. The present study investigated the effects of CDCA4 knockdown on the regulation of triple negative breast cancer (TNBC) cell proliferation in vitro and in vivo . Human TNBC MDA-MB-231 cells were subjected to CDCA4 expression knockdown using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In a previous study, Hayashi et al showed that CDCA4 participated in cell proliferation [11]. Moreover, CDCA4 is involved in the triple-negative breast cancer (TNBC) cells [36], and it is shown that RNA interference of CDCA4 markedly increases cell apoptotic rate. In addition, one recent study suggests that CDCA4 enhances human BC cell proliferation and reduces their apoptosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Hayashi et al showed that CDCA4 participated in cell proliferation [11]. Moreover, CDCA4 is involved in the triple-negative breast cancer (TNBC) cells [36], and it is shown that RNA interference of CDCA4 markedly increases cell apoptotic rate. In addition, one recent study suggests that CDCA4 enhances human BC cell proliferation and reduces their apoptosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that different pathogen or parasite exposure in freshwater and seawater has been a driving force for selection on disease resistance (a topic discussed in more detail by Zueva et al (2018)). Not much is known about cdca4, however, the gene encodes a regulator of transcriptional activation involved in cell proliferation (Hayashi et al, 2006) and has been shown to interact with p53 to promote apoptosis upon DNA damage (Hsieh et al, 2002;Pang et al, 2019). In humans, tRNA copy number variations can have phenotypic effects (Iben & Maraia, 2014;Kirchner & Ignatova, 2015).…”
Section: The Most Differentiated Selective Sweep On Chr 15mentioning
confidence: 99%
“…Recently some researchers revealed that CDCAs might contribute to the cancer progression. Previous studies had shown that some members of this gene family might be up-regulated in breast cancer, lung adenocarcinoma and pancreatic adenocarcinoma [5][6][7][8][9][10][11][12][13][14][15][16]. And high expression levels of these genes were identified as poorly predictive factors of survival in these cancers [17,18].…”
Section: Introductionmentioning
confidence: 99%